INVESTIGATION OF SOME BIOCHEMICAL PARAMETER IN FIVE DIFFERENT SALONUM MELONGENA L. CULTIVARS - MUKHTAR, ZULAIHA GIDADO (Fırat Üniveristesi, 2021)
Bu çalışmada, Türkiye (koyu ve açık patlıcan) ve Nijerya'dan (beyaz bahçe yumurtası, acı elma ve acı domates) örneklenen çeşitli fenotiplere sahip beş patlıcan türündeki bazı biyokimyasal parametrelerin belirlenmesi ve karşılaştırılması amaçlanmıştır. Amino asit, vitamin ve stres biyomarker konsantrasyonları; ile ABTS ve DPPH testlerine dayalı toplam fenolik (TPC) ve flavonoid madde içerikleri (TFC) ile antioksidan kapasiteleri (TAC) HPLC ve spektrofotometrik olarak araştırılmıştır. Elde edilen sonuçlardan, örneklerdeki amino asit miktarlarının 23.5 - 33625 ?g/g dw arasında değistiği; bunlar arasında en düşük ve en yüksek miktarın sırasıyla lösin ve lizin olduğu belirlenmiştir. RDA'ya göre, tüm çeşitler histidin, lizin, metiyonin, fenilalanin, treonin ve triptofan açısından günlük diyet yeterliliğine katkıda bulunabilir. Aksine, beyaz bahçe yumurtası ve acı elma çeşitlerinde yeterli miktarda valin bulunurken, koyu patlıcan, açık patlıcan ve acı domates çeşitleri besin açısından daha düşük değerlere sahiptir. Ayrıca, tüm çeşitlerde lösin miktarırın düşük olduğu gözlenmiştir. Elde edilen sonuçlardan, bütün çeşitlerin suda çözünür vitaminler bakımından iyi birer vitamin kaynağı olduğu; bazıları A vitamini (beyaz bahçe yumurtası, acı elma ve acı domates) ve E vitamini (siyah patlıcan ve acı domates) bakımından önemli iken, likopen bakımından daha fakir olduğu bulunmuştur. 4-Hidroksinonenal miktarının, aşağıdaki artan sırada olduğu gözlenmiştir; acı elma

This study aimed to determine and compare varietal variations in five eggplant varieties with diverse phenotypes sampled from Turkey (dark and light eggplant) and Nigeria (white garden egg, bitter apple and bitter tomato). The concentrations of amino acids, vitamins, and stress biomarkers analysed using HPLC; and the total phenolic content (TPC), total flavonoid content (TFC) total antioxidant capacities (TAC) based on ABTS and DPPH assays using spectrophotometer were investigated and compared. Our findings determined the concentration of 19 amino acids in all varieties ranging from 23.5 – 33625.4 ?g/g DW, with the lowest and highest determined for leucine and lysine, respectively. Based on RDA, all of the varieties can contribute to dietary adequacy in terms of histidine, lysine, methionine, phenylalanine, threonine, tryptophan and white garden egg and bitter apple varieties had adequate amounts of valine. Likewise, all the varieties were nutritionally low in leucine. Additionally, the concentration of 12 vitamins determined, ranging from 0.13 – 2543.02 ?g/g DW with the lowest and highest for vitamin A and vitamin B5, respectively. Relative to the RDA, all the varieties are excellent sources of the water-soluble vitamins; some are nutritionally significant in terms of vitamin A (white garden egg, bitter apple and bitter tomato) and vitamin E (dark eggplant and bitter tomato). 4-Hydroxynonenal ranging from 24.6 – 48.3 µg/g DW was determined, with the lowest and highest for bitter apple and white garden egg respectively. The concentration of MDA ranging from 1.50 -18.41µg/g DW. All the varieties of eggplant used in this study contained both reduced (GSH) and oxidized (GSSG) forms of glutathione. GSH levels were found to range from 364.85 – 5930.32 µg/g. The white garden egg had the highest amount of both GSH and GSSG while the bitter tomato and dark eggplant had the lowest GSH and GSSG levels, respectively. The TPC (706.30 – 1260.32 ?g GAE/g) was determined in the following order -light eggplant < bitter tomato< bitter apple< dark eggplant< white garden egg. While the TFC (167.50 – 356.51 ?g QE/g) was determined in the following order- bitter apple < light eggplant< bitter tomato< dark eggplant< white garden egg. For the TAC, the scavenging activity for the ABTS radical (365.44 – 809.52 µg/g) was higher than for the DPPH radical (83.86 - 243.02 µg/g). The white garden egg exhibited the highest TAC in both assays while the bitter tomato and bitter apple had the lowest in the ABTS and DPPH assays, respectively. Our findings highlighted a wide disparity in the levels of the nutrients, stress biomarkers, TPC, TFC and TAC within and between the eggplants sampled from the different countries attributed to varietal difference and growth conditions. This presents opportunities for dietary inclusion and other stakeholders to select and develop improved plant varieties
Beş farklı Salonum melongena L. çeşidinde bazı biyokimyasal parametrelerin incelenmesi
Keywords: Kimya